Greedy Non-Intrusive Reduced-Order Model's application in dynamic blowing and suction flow control to suppress the flow separation. (15th April 2022) - Wang, Chen; Qi, Zheng; Zheng, Yu; Duan, Huishen; Chen, Anhong; Du, Fan; Xu, Jiakuan; Li, Guoshu; Xia, Qiang
Abstract: The Greedy Non-Intrusive Reduced-Order Model (GNIROM) is applied in dynamic blowing and suction's flow control to suppress the GAW1 airfoil's flow separation. The effects of the uniform blowing and uniform suction on the flow fields and aerodynamic coefficients have been studied firstly. By comparing a uniform suction control with a dynamic blowing and suction control, it has been found that the dynamic blowing and suction can provide a higher lift coefficient and a lower energy loss. Finally, for the sake of achieving an optimal dynamic blowing and suction control, an optimization of the dynamic blowing and suction's parameters is taken based on the GNIROM, consisting of a Non-Intrusive ROM (NIROM) built by the two-level POD and Radial Basis Function (RBF), and the relative greedy method. A cost function has been proposed by considering suppressing the flow separation, improving the lift-drag characteristics and reducing the energy loss together. The GNIROM has been built for unsteady vorticity fields with the parameters of the dynamic blowing and suction varying. Based on the GNIROM's approximation, the optimal control parameters' values have been determined quickly. Compared to the initial dynamic blowing and suction control, the optimal one has reduced the drag coefficient by 43.4 percents and the energy loss by 42 percents. Highlights: A Greedy Non-Intrusive Reduced-Order Model. The research of blowing and suction flow control to suppress the flow separation. An optimization of dynamic blowing and suction based on GNIROM.